Autism Spectrum Disorders Advances at the End of the Second Decade of the 21st Century - Fitzgerald, Michael (IntechOpen, 2019)
The changing face of psychiatry and clinical psychology is mostly illustrated by the hugely increasing prevalence of autism spectrum syndrome. There has been a rapid advance in research, and books like this are therefore necessary. The book focuses on controversies in the diagnosis of autism with an examination of stercobilin, autism, and gastrointestinal disease. It also focuses on an exploration of scalp acupuncture as a possible treatment. There is also critical examination of autism in the classroom and an investigation into an unusual phenomenon seen in Africa called ?nodding syndrome.?